A novel snow transport model for analytically investigating effects of wind exposure on flat roof snow load due to saltation. Issue 210 (March 2021) - Qiang, Shengguan; Zhou, Xuanyi; Gu, Ming; Kang, Luyang
Abstract: This paper introduces a novel snow transport model for the analytical simulation of wind-induced snow transport on flat roofs. In the novel model, the differences between precipitation and deposited snow particles on roofs, including the differences in threshold friction velocity and fetch distance for saturated drifting state, are considered. Thus, snow drifting on a roof is divided into drifting without and during snowfall. The effects of terrain category and roof height are also considered using the friction velocity on roofs to compute snow transport rate instead of directly using the wind speed data reported by weather stations. Parametric analysis and case study are conducted to explain the novel model in detail and compare the results with those obtained from the model developed by O'Rourke et al. (2005). The estimated fetch distance for saturated snow drifting by the proposed approach in this study ranges from zero to thousands of meters, which is consistent with field measurement results and more reasonable than the use of constant values. Results of the case study indicate that the proposed snow transport model might be more reasonable because the effects of more factors are considered. Highlights: A novel snow transport model considering the effects of wind exposure on snow load is introduced. Snow drifting is divided into drifting without snowfall and drifting during snowfall. Methods for estimating fetch distance for saturated drifting are developed. Impacts of terrain and roof height are taken into consideration.